C-Myc downregulation is required for preacinar to acinar maturation and pancreatic homeostasis. Issue 4 (3rd February 2017) - Sánchez-Arévalo Lobo, Victor J; Fernández, Luis César; Carrillo-de-Santa-Pau, Enrique; Richart, Laia; Cobo, Isidoro; Cendrowski, Jaroslaw; Moreno, Ulisses; del Pozo, Natalia; Megías, Diego; Bréant, Bernardette; Wright, Christopher V; Magnuson, Mark; et al.
Abstract : Background and aims: c-Myc is highly expressed in pancreatic multipotent progenitor cells (MPC) and in pancreatic cancer. The transition from MPC to unipotent acinar progenitors is associated with c-Myc downregulation; a role for c-Myc in this process, and its possible relationship to a role in cancer, has not been established. Design: Using coimmunoprecipitation assays, we demonstrate that c-Myc and Ptf1a interact. Using reverse transcriptase qPCR, western blot and immunofluorescence, we show the erosion of the acinar programme. To analyse the genomic distribution of c-Myc and Ptf1a and the global transcriptomic profile, we used ChIP-seq and RNA-seq, respectively; validation was performed with ChIP-qPCR and RT-qPCR. Lineage-tracing experiments were used to follow the effect of c-Myc overexpression in preacinar cells on acinar differentiation. Results: c-Myc binds and represses the transcriptional activity of Ptf1a . c-Myc overexpression in preacinar cells leads to a massive erosion of differentiation. In adult Ela1-Myc mice: (1) c-Myc binds to Ptf1a, and Tcf3 is downregulated; (2) Ptf1a and c-Myc display partially overlapping chromatin occupancy but do not bind the same E-boxes; (3) at the proximal promoter of genes coding for digestive enzymes, we find reduced PTF1 binding and increased levels of repressive chromatin marks and PRC2 complex components. Lineage tracing of committed acinar precursors reveals that c-Myc overexpression does not restore multipotency but allows the persistence of a preacinar-like cell population. In addition, mutant KRas can lead to c-Myc overexpression and acinar dysregulation. Conclusions: c-Myc repression during development is crucial for the maturation of preacinar cells, and c-Myc overexpression can contribute to pancreatic carcinogenesis through the induction of a dedifferentiated state.